Smart food: novel foods, food security, and the Smart Nation in Singapore. - Stevens, Hallam; Ruperti, Yvonne (Food, Culture & Society, 2024)
In December 2020, Singapore made global headlines by being the first country to approve the commercial sale of lab grown meat. This approval was part of an effort by the city state to intensify the development of novel foods on the island. This paper describes this recent growth of novel food companies in Singapore. Singapore's novel food policies ostensibly aim to create food security for its citizens. We argue that the embrace of the technology that surrounds novel foods also aligns with Singapore's vision of building a "smart nation." Although food is not a digital technology, the approaches to novel foods being taken in Singapore share many parallels with the rollout of digital technology. These parallels can be seen in the domains of standardization, regulation, intellectual property, data-gathering, and training. We anticipate that these shifts in procurement, regulation, consumption of foods, may ultimately challenge traditional food pathways and Singapore's food identity.